Physical activity in a pandemic: A new treatment target for psychological therapy. (25th June 2020) - Diamond, Rowan; Waite, Felicity
Abstract : The COVID‐19 pandemic and its management are placing significant new strains on people's well‐being, particularly those with pre‐existing mental health conditions. Physical activity has been shown to improve mental as well as physical health. Increasing activity levels should be prioritized as a treatment target, especially when the barriers to exercise are greater than ever. Promoting physical activity has not traditionally been the remit of psychologists. Yet psychological theory and therapeutic techniques can be readily applied to address physical inactivity. We present theoretical perspectives and therapy techniques relating to (1) beliefs about physical activity, (2) motivation to be physically active, and (3) the sense of reward achieved through being physically active. We outline strategies to initiate and maintain physical activity during the COVID‐19 pandemic, thereby benefitting mental and physical health. COVID‐19 is demanding rapid and substantial change across the whole health care system. Psychological therapists can respond creatively by addressing physical activity, a treatable clinical target which delivers both mental and physical health benefits. Practitioner points: Physical activity is essential for our mental and physical health. Yet COVID‐19 presents novel barriers to physical activity. Psychological theory and techniques to address beliefs, motivation, and reward can be applied to increase physical activity during COVID‐19. Physical activity is an important clinical target to sustain and improve mental health, especially in the current pandemic.